MENAFSIR ULANG KITAB KUNING: ARAH BARU RISET TRANSFORMATIF PESANTREN DI INDONESIA - Ma'rup (Journal Khafi : Journal Of Islamic Studies, 2025)
This paper examines the contextualization of kitab kuning (classical Islamic texts) and the transformative research tradition that has evolved within Indonesian pesantren (Islamic boarding schools). The long historical journey of pesantren in the Indonesian archipelago has produced profound social transformations and significantly influenced the religious life of Muslim communities. According to Bruinessen, pesantren have successfully established a great tradition in Islamic education rooted in the study of classical texts, commonly referred to as kitab kuning. As institutions that nurture both intellectual heritage and research culture, pesantren hold substantial potential in addressing contemporary and future societal challenges. The research paradigm within pesantren possesses unique characteristics that distinguish it from conventional research approaches. These distinctions arise from divergent ontological, epistemological, methodological, and axiological constructions, which are deeply grounded in the social history, core values, and intellectual traditions of the pesantren itself.